Turbidity and sediment dynamics measured with SediMeter sensors to assess biofouling effects in Biscayne Bay, Miami, USA (May–July 2017) - Lin, Chin Yik; Lam, Su Shiung; Er, Jenn Wei; Lee, Wah Sza; Jia Hui, Ang; Erlingsson, Ulf; Gan, Yew Sun; Yee, Woei Shyan (In: Lin, CY et al. (2025): Utilizing optical backscatter sensor and sediment traps for measuring sediment dynamics in low energy marine environment [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984064, 2025)
This dataset captures turbidity and sediment dynamics using SediMeter (SM) sensors in Biscayne Bay, Miami, USA (25°35.5385′N, 80°10.5024′W) from May to July 2017. The observations focused on biofouling effects on sediment flux measurements and turbidity readings. Two SM units, one equipped with an anti-biofouling cleaning system and one without, were deployed side-by-side in a sandy, seagrass-rich area known as the "safety valve." Turbidity was measured in Formazin Backscatter Units (FBU) at 2-minute intervals. Data revealed significant turbidity variation influenced by tidal events, highlighting the substantial impact of biofouling on instrument readings. The dataset is critical for validating the reliability of turbidity measurements in marine environments subject to biological interference.
Keywords: marina; sedimentation rate; sediment fluxes; Sediment trap; SediMeter; turbidity